Early manifestation of Pott’s disease in a 3-years-old child: Case Report - anestessia, ira juliet (Jurnal Biomedika dan Kesehatan, 2026)
Introduction and importance Pott’s disease is an extra-pulmonary manifestation of TB described in 1779 by Percivall Pott which is the most common form of skeletal TB particularly in children. The manifestation leads to bony destruction, characterized by back pain, fever, anorexia, night sweats, weight loss, and paraparesis, in very low progression. Case presentation A 3-year-old boy with alternating walk pattern and pain in his lower leg when walking more than 100 meters and walks slightly bent over. A bony protrusion slightly palpated in thoracic area, and Mantoux test results were positive. A thorax X-ray revealed a paravertebral mass, and an MRI showed multiple level vertebral body disintegration on thoracic 7 and thoracic 8 with a paravertebral abscess in the thoracic area. The patient is receiving conservative treatment, including TB drugs, thoracolumbar orthosis, and calcium Discussion It is important to recognize early symptoms of spinal tuberculosis in children to prevent the deterioration of neurological status and kyphotic deformity. In these cases, slight alteration of walking pattern without concomitant symptoms and significant laboratory findings give us significant changes on MRI. Early diagnosis might give favoured results on conservative management Conclusions The most prevalent type of skeletal tuberculosis is Pott's disease, and incidence in youngsters varies. Majority of patients presented with anorexia, fever, night sweats, weight loss, rachialgia, and paraplegia. Early discovery of the disease's mild signs may help to stop its progression. Keyword Infection, Pott’s disease, spinal tuberculosis, child, kyphotic deformity